Measuring nanoscale diffusion dynamics in cellular membranes with super-resolution STED–FCS - Sezgin, E; Schneider, F; Galiani, S; Urbančič, I; Waithe, D; Lagerholm, B; Eggeling, C (Springer Nature, 2019)
Super-resolution microscopy techniques enable optical imaging in live cells with unprecedented spatial resolution. They unfortunately lack the temporal resolution required to directly investigate cellular dynamics at scales sufficient to measure molecular diffusion. These fast time scales are, on the other hand, routinely accessible by spectroscopic techniques such as fluorescence correlation spectroscopy (FCS). To enable the direct investigation of fast dynamics at the relevant spatial scales, FCS has been combined with super-resolution stimulated emission depletion (STED) microscopy. STED–FCS has been applied in point or scanning mode to reveal nanoscale diffusion behavior of molecules in live cells. In this protocol, we describe the technical details of performing point STED–FCS (pSTED–FCS) and scanning STED–FCS (sSTED–FCS) measurements, from calibration and sample preparation to data acquisition and analysis. We give particular emphasis to 2D diffusion dynamics in cellular membranes, using molecules tagged with organic fluorophores. These measurements can be accomplished within 4–6 h by those proficient in fluorescence imaging.